Foreign policy : intervention, involvement, or isolation? - Wolf, Alvin 1935- (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
Presents divergent viewpoints regarding the United States' past, present, and future political, economic, humanitarian, and diplomatic involvements with other nations
Bibliography: p. 115-120.
Keywords: United States -- Foreign relations -- 1945; United States -- Relations -- Foreign countries